Water quality–pipe deposit relationships in Midwestern lead pipes. Issue 2 (4th March 2019) - Tully, Jennifer; DeSantis, Michael K.; Schock, Michael R.
Abstract : The conventional wisdom of lead‐scale solubility has been built over the years by geochemical solubility models, experimental studies, and field sampling using multiple protocols. Rarely have the mineral phases from scales formed in real‐world drinking water lead service lines (LSLs) been compared with theoretical predictions. In this study, model predictions are compared with LSL scales from 22 drinking water distribution systems. The results show that only 9 of the 22 systems had LSL scales that followed model predictions. The remaining systems had unpredictable scales, some with unknown lead release characteristics, demonstrating that predicting scale formation and lead release solely by models cannot be relied on in all cases to protect human health. Therefore, for many systems with LSLs, pilot studies with existing LSL scales will be necessary to evaluate and optimize corrosion control, and correspondingly, appropriate residential water sampling will be needed to demonstrate consistent and optimal system corrosion control.